If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3d+16=-20-6d
We move all terms to the left:
3d+16-(-20-6d)=0
We add all the numbers together, and all the variables
3d-(-6d-20)+16=0
We get rid of parentheses
3d+6d+20+16=0
We add all the numbers together, and all the variables
9d+36=0
We move all terms containing d to the left, all other terms to the right
9d=-36
d=-36/9
d=-4
| 8+12x=40 | | 4*(x-1)-3*(x+3)=3*x+5 | | 3x2-28x+9=0 | | -7b-2=4-9b | | -2x2+20x-46=0 | | 21v=168 | | .6667x-6=18 | | 30=t/25 | | 10+5g=-g-8 | | 30=t25 | | -9-y=-4y+9 | | 17=t−42 | | 7x+40=-2 | | 7x2-6x+2=0 | | b+38=61 | | -6+2g=7g+9 | | -2m-3=-10-9m | | 7x2-22x+3=0 | | r+6=6+r | | 7x2-35=0 | | 0.5x+3=-9 | | 5(3x+9)-2x=15x-2(x-5)+10 | | -4c+9=9-4c | | -10-6h=-10-5h | | 10-8z=-8z+10 | | -4(2x-8)=5+7(-2x+7) | | -8f-8=-8f-9 | | -7q+6=6-7q | | 7(4x-2)=2(-3x-8)-24 | | 2(x+16=50 | | -2t+6=3-2t | | 2+(4x)/3(-7)=1 |